CARPE DIEM IN ANDREW MARVELL’S POEM TO HIS COY MISTRES - Arifuddin Arifuddin; Hidayati Hidayati; Misla Geubrina; Hendra Mulia (Universitas Islam Sumatera Utara, 2022)
Carpe Diem derives from Latin which, in English, means seize the opportunity by enjoying the present time and trusting the least possible to the future. The future is formed through the present. Carpe Diem is the main theme in Andrew Marvell's To His Coy Mistress and is the object of this research. The poet's view of the transience of the world is clearly illustrated referring to the limitations of time and space for humans; Thus, every available moment must be utilized. This research is conducted using descriptive qualitative method related to social phenomena and based on the Carpe Diem terminology and supported by the concept of taking advantage of existing opportunities. These two concepts basically refer to a single notion which states that opportunities will not come repeatedly. The results show that there are two forms of Carpe Diem in this poem, namely in matters of love and sex and both are conveyed by the male lover to his lady by using the arguments that they are mortal and everything they have is limited. Relationships of love and sex must be carried out immediately because only then can they see, feel and enjoy the beauty of love and the pleasures of sex.